Planetary boundaries for a blue planet. Issue 11 (November 2017) - Nash, Kirsty; Cvitanovic, Christopher; Fulton, Elizabeth; Halpern, Benjamin; Milner-Gulland, E.; Watson, Reg; Blanchard, Julia
Abstract Concepts underpinning the planetary boundaries framework are being incorporated into multilateral discussions on sustainability, influencing international environmental policy development. Research underlying the boundaries has primarily focused on terrestrial systems, despite the fundamental role of marine biomes for Earth system function and societal wellbeing, seriously hindering the efficacy of the boundary approach. We explore boundaries from a marine perspective. For each boundary, we show how improved integration of marine systems influences our understanding of the risk of crossing these limits. Better integration of marine systems is essential if planetary boundaries are to inform Earth system governance. Incorporating marine biomes into the planetary boundaries framework promotes integrated understanding of biophysical limits and earth system governance.